The anxious generation [compact disc, unabridged] : how the great rewiring of childhood is causing an epidemic of mental illness - Haidt, Jonathan (Penguin Random House, 2024)
Social psychologist Jonathan Haidt lays out the facts about the epidemic of teen mental illness that hit many countries at the same time. He then investigates the nature of childhood, including why children need play and independent exploration to mature into competent, thriving adults. He explains why social media damages girls more than boys and why boys have been withdrawing from the real world into the virtual world, with disastrous consequences for themselves, their families, and their societies. Haidt describes steps that parents, teachers, schools, tech companies, and governments can take to end the epidemic of mental illness and restore a more humane childhood.